Central Bank's Action and Communication - Romain Baeriswyl (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2007)
This paper contributes to the ongoing debate about the welfare effect of public information. In an environment characterized by imperfect common knowledge and strategic complementarities, Morris and Shin (2002)argue that noisy public information may be detrimental to welfare because public information is attributed too large a weight relative to its face value since it serves as a focal point. While this argument has received a great deal of attention in central banks and in the financial press, it considers communication as the sole task of a central bank and ignores that communication usually goes with a policy action. This paper accounts for the action task of a central bank and analyzes whether public disclosure is beneficial in the conduct of monetary policy when the central bank primarily tries to stabilize the economy with an instrument that is optimal with respect to its perhaps mistaken view. In this context, it turns out that transparency is particularly beneficial when central bank's information is poorly accurate because it helps reducing the distortion associated with badly suited policies.
urn:nbn:de:bvb:19-epub-1381-1
Keywords: D82; E52; E58; 330; differential information; monetary policy; transparency; Zentralbank; IKT-Politik; Wohlfahrtsanalyse; Theorie